Analysis of the PPP and the UIP in Iceland Under Disparate Monetary Regimes - Gunnar Sigurðsson Ísdal 1992- (2019)
In the case of small open economies like Iceland, exchange rate stability is one of the key determinants of achieving the primary goals of monetary policy (price stability). Monetary policy in Iceland has faced obstacles in the past century due to high vulnerability to external shocks and weak policy frameworks. This thesis aims to investigate international transmission effects between countries through determination of exchange rate, interest rates, and prices, as assumed by the purchasing power parity (PPP) and the uncovered interest rate parity (UIP) relation during disparate monetary regimes in Iceland. The empirical study is based on the analysis conducted by Johansen & Juselius (1992) for the UK using the multivariate error correction model, where the short-run dynamics and the long-run relationships are estimated between economies. The model is five-dimensional and contains the consumer price index (CPI) and short-term interest rates in the economic areas and the exchange rate between them. This study focuses on the long-run equilibrium between Iceland and developed large economies; the Eurozone (EUR), the United Kingdom (UK) and the United States (USA). The PPP and UIP are shown to exist in some form prior to the financial crisis for the UK and the Eurozone, and for the US during capital controls. Furthermore, the results indicate that there is a relationship between the goods and financial market between the US during capital controls but next to none for the Eurozone or the UK. Í smáum opnum hagkerfum eins og Íslandi, er gengisstöðugleiki einn af megin áhrifaþáttum í því að stuðla að meginmarkmiði peningamálastefnu (verðstöðugleiki). Erfitt hefur verið að framfylgja peningamálastefnu á Íslandi síðastliðna öld vegna berskjöldunar gagnvart ytri áhrifum og veikrar stefnumörkunar í peningamálum. Í þessari ritgerð er kaupmáttarjafnvægi (PPP) og óvarið vaxtajafnvægi (UIP) metið fyrir Ísland gagnvart öðrum löndum fyrir ólík tímabil í peningamálastefnu hér á landi. Rannsóknin er byggð á greiningu sem var ...